Pengaruh Frekuensi Latihan Aerobic Terhadap Nilai V02max Pada Taekwondoin Dojang Koguryo Manahan Surakarta - Samade, Vivi Julyanti; , Isnaini Herawati , S.Fis., M.Sc; , Wijianto SST.FT., M.OR; , Dwi Kurniawati, SSt.FT (2017)
Abstracts Some exercises can improve V02max include exercises during their appearance, are worth at least 2/3 (70%) of all energy in use are provided through aerobic power management; it means that there is a maximum of 30% of anaerobic power management that can not be produced by aerobic power management, for example run> 8 minutes or if it is converted into meters to> 3000 m. Frequency of exercise can affect the effects of exercise result, frequent and repetitive exercise regularly can increase the value V02max be maximal. This study aim is to know the effect of differences in the frequency of aerobic exercise on V02max value of Taekwondoinin DojangKoguryo Manahan Surakarta. This research is using cross sectional approach and observational designs. The first group with training frequency <3 times/week and the second group with> 3 times/ week. There are 24 samples that used in this study, the sampling technique with a total sampling technique that used existing population criteria of inclusion and exclusion. The results of Mann Whitney test is a significant difference with p = 0.01 between the V02maxvalue of exercisegroup with <3 times / week frequency andexercise group with > 3 times / week frequency, from these results V02max value ofthe exercisegroup with > 3 times / week frequencyhad V02max better than the exercise group with <3X / weekfrequency. There is an effect of aerobic exercise frequency to the V02maxvalue ofTaekwondoin in Dojang Koguryo Manahan Keywords: Aerobic exercise, exercise frequency and V02max